1997
DOI: 10.1111/j.1439-0442.1997.tb01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Pancreas Specific Protein Assays, TLI(Trypsin‐Like Immunoreactivity), PASP (Pancreas Specific Protein) and CA 19–9 (Glycoprotein) for use in the Diagnosis of Canine Pancreatitis

Abstract: Summary Three radioimmunoassays (RIA) for the pancreas specific proteins TLI, PASP and CA 19–9 were evaluated in serum from normal control dogs (n = 40) and dogs with pancreatitis (n = 20). Statistically significant differences (P < 0.05) were found for serum TLI and PASP levels between the control and pancreatitis groups. However, only 3/20 dogs with pancreatitis had serum TLI concentrations greater than the highest concentration in control dogs. Concentrations of PASP in serum were higher in 15/20 dogs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The cTLI assay has been described as a highly sensitive and specific test for the assessment of exocrine pancreatic insufficiency, however, the performance characteristics of the assay are suboptimal for the diagnosis of pancreatitis, and the low sensitivity of this assay was confirmed in this study. Measurement of serum amylase activity was the least sensitive test for the diagnosis of mild or moderate to severe pancreatitis; however, the high specificity for this test and the cTLI can be explained by the relatively low numbers of dogs lacking histopathologic evidence of pancreatitis, and the fact that these tests were within the reference interval for all these dogs.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The cTLI assay has been described as a highly sensitive and specific test for the assessment of exocrine pancreatic insufficiency, however, the performance characteristics of the assay are suboptimal for the diagnosis of pancreatitis, and the low sensitivity of this assay was confirmed in this study. Measurement of serum amylase activity was the least sensitive test for the diagnosis of mild or moderate to severe pancreatitis; however, the high specificity for this test and the cTLI can be explained by the relatively low numbers of dogs lacking histopathologic evidence of pancreatitis, and the fact that these tests were within the reference interval for all these dogs.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, increases in serum lipase activity occur in dogs with renal and hepatic disease in the absence of pancreatic inflammation . Measurement of serum trypsin and trypsinogen‐like immunoreactivity (TLI) is highly sensitive and specific for the diagnosis of exocrine pancreatic insufficiency; however, this assay has limited value for the diagnosis of canine pancreatitis . More recently, a radioimmunoassay (RIA) and enzyme‐linked immunosorbent assay (ELISA) were developed and validated for the measurement of canine pancreatic lipase (cPL) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The etiopathogenesis of canine AP remains unclear and its diagnosis can be challenging. Increased serum amylase, lipase, and canine trypsin‐like immunoreactivity (cTLI) measurements have been relied upon for AP diagnosis in dogs; however, the diagnostic specificity of these variables is low . Abdominal radiographs are nonspecific for canine pancreatitis, while the sensitivity of abdominal ultrasonographic examination has been reported to reach 68% .…”
Section: Introductionmentioning
confidence: 99%
“…The only modest specificity and sensitivity of amylase and lipase has resulted in attempts to find more specific assays including trypsin-like immunoreactivity, pancreasspecific protein, CA 19-9 glycoprotein, trypsinogen activation peptide, alpha-2-macroglobulin, trypsin-alpha-1-proteinase and C reactive protein (Archer et al 1997;Mansfield et al 2003;Nakamura et al 2008;Steiner 2003), none of which have been found to be clinically valuable.…”
Section: Discussionmentioning
confidence: 99%